NU Kyai's Thoughts On Professional Zakat And Its Implementation In Zakat Payment At The Amil Institution In Jember (Sharia Faculty Islamic Economic Law Study Department, 2025)
This research examines the thoughts of Nahdlatul Ulama (NU) Kyai in Jember regarding professional zakat and its implementation in zakat payment through zakat management institutions. Using a phenomenological qualitative method, this research explores the mindset of NU kyai, encompassing structural and cultural perspectives by involving six influential NU figures in Jember Regency. The results show a significant difference of opinion. Supporters argue that professional zakat is an important instrument for economic equality, poverty alleviation, and the improvement of community welfare. They base their views on the principle of qiyas (analogy) from religious texts. On the other hand, the opposing group believes that the obligation of professional zakat lacks a strong legal basis in the Qur'an or Hadith and prioritizes voluntary donations or charity. In its implementation, the role of zakat management institutions in Jember faces challenges such as a lack of public trust, sectoral egos among institutions, and issues of transparency and credibility in the management of zakat funds. This research emphasizes the need for collaboration among zakat management institutions, strengthening credibility, and transparency in zakat management to enhance community participation and the effectiveness of zakat distribution. The thoughts of NU kyai have a significant influence on the patterns of zakat distribution by the community, making them a key element in the optimization of professional zakat in Jember.